Hijrah and Muslim Medium Society Movements In Indonesia: Study of The Majelis Gaul Dakwah Movement in Jember City - Sa’diyah, Miftahus; Supandi, Ach. Faqih; Aini, Nur (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
The phenomenon of the hijrah movement is now a trend in Muslim middle society. The spread of the hijrah trend shows that this movement has the ability to attract its members, especially targeting young people. This movement is active in conducting millennial religious studies with a modern approach and through online studies through social media as a medium of da'wah da syi'ar. The purpose of this paper is to describe the trend of the migration movement in the city of Jember. The method used in this research is a qualitative approach with a research library. The results showed that the migration and the Muslim Middle-scale community movement were able to target millennial children because the topic of hijrah that was raised attracted more millennial attention, one of which was discussing human relations with Allah, but now the issue is more contextual such as problems with relationships with fellow humans even to fashion.